Minors in clinical trials: balancing ethics, rights and medical innovation - Coronato, Irene (Bioethica, 2025)
This report explores the complex intersection of medical innovation, ethics and the rights of minors participating in clinical trials. While pediatric clinical research is fundamental for developing effective treatments, it also raises significant ethical concerns due to the vulnerability of this population, which stems from their reliance on parents and caregivers and their limited ability to fully comprehend the procedures involved. The report addresses key issues such as the principle of informed consent and the requirement of assent, drawing from the legal framework governing this area. This includes instruments such as the UN Convention on the Rights of the Child and the EU Clinical Trials Regulation. The guiding principle in all pediatric decisions is the child’s best interest, which ultimately shapes ethical and legal parameters of clinical research. Risk/benefit assessments are crucial and must inform all stages of the clinical trial. Other essential safeguards include the right to withdraw from a trial and the right to be informed or not to be informed about one’s medical condition. The report also examines situations of parental disagreement. The ethical role of ethics committees is highlighted, particularly their responsibility to ensure the legitimacy of consent and prevent undue influence. The report stresses the need for these committees to include experts in pediatric ethics and child development. Practical challenges are also explored, such as the difficulty of assessing risk, particularly with infants and children who cannot articulate discomfort. Innovative multimedia methods for explaining trials to children and parents are examined as ways to improve understanding and transparency. Special attention is given to modern controversial practices, including the use of healthy children as stem cell donors for their siblings and the use of hypothermia in cases of perinatal hypoxic ischemic encephalopathy. The report concludes by arguing that excluding minors from clinical trials in the name of protection would unjustly deprive them of access to potentially life-improving treatments. Instead, clinical trials must be conducted not on children but with children, ensuring that respect of their rights, needs and demands is at the heart of every decision.